IMPLEMENTASI PERENCANAAN STRATEJIK PEMBELAJARAN MELALUI PEMBELAJARAN BERDIFERENSIASI MENGGUNAKAN MEDIA BERBASIS TIK UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DIDIK - Zaman, Badri; Abuy, Abuy; Amalia, Nelly; Yoseptry, Ricky; Masrukoyah, Enyi; Setiani, Ira (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This study aims to conduct an in-depth analysis and implement strategic learning planning through a differentiated learning approach by utilizing Information and Communication Technology (ICT)-based media to enhance students' learning interest. A case study was conducted in the Tegallega Cluster, Warungkondang Sub-district, Cianjur Regency, which includes several elementary schools with diverse student characteristics. This research is motivated by the problem of low student learning interest caused by the monotony of conventional teaching strategies and the limited use of media relevant to the digital era, which makes learning less engaging and fails to meet students' individual needs. This study uses a qualitative method with a descriptive approach. Data were collected through direct classroom observations, in-depth interviews with teachers and school principals, questionnaires for students and parents, and document studies related to previously implemented lesson plans. Data analysis was conducted thematically to explore patterns and the effectiveness of implementing a differentiated learning strategy designed based on students' varying abilities, learning styles, and interests. ICT-based media, such as interactive learning applications, educational videos, multimedia presentations, and online platforms like Learning Management Systems (LMS), were used as primary tools to support the learning process. The results of the study indicate that the implementation of differentiated learning using ICT-based media had a significant positive impact on increasing students' learning interest. The teachers involved in the study were able to develop more innovative and flexible lesson plans by adapting the content and approach based on the needs of students in heterogeneous classrooms.